Speaking Up without Freaking Out - Nurul Adillah (Edukasi, 2019)
It has been reported that language learners use various strategies in learning a second or foreign language. And a lot of research has been done in this area. However, few studies have explored the impact of using scaffolding impromptu speaking activities in ESL classroom on alleviating speaking anxiety. Thus, the current study is an attempt to investigate whether scaffolding impromptu speech activities could help the students to perform better during oral presentation and reduce their speaking anxiety. At the beginning of the study, the students were asked to answer online questionnaire on speaking anxiety experience while holding an oral presentation tasks or assessment. 38 undergraduate students did the prepared impromptu speaking activities such as they have to do self-video recorded, impromptu speech in group and online discussion. This intervention was carried out for six weeks. After that, another online questionnaire on the effectiveness of scaffolding impromptu speaking activities was distributed. However, we only received 25 responses from the participants. Besides that, participants' views about the impromptu speaking activities were also examined through focus group interview. The results of the study indicated that by scaffolding impromptu speaking activities in ESL classroom, the students were able to reduce their speaking anxiety and enhance their oral presentation skill.